2022
DOI: 10.1002/jcop.22863
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19‐related anxiety: How do coping and optimism relate to substance use in African–American young adults?

Abstract: The COVID–19 pandemic has greatly affected college students nationwide. Recent research suggests that the COVID–19 pandemic has disproportionately impacted African–American young adults. The infection case rates, hospitalizations, and death rates in African–American populations are 2–5 times higher than among White populations. The intergenerational trauma and systemic racism that African–Americans have faced in past and present times have fomented conditions that lead to vulnerability within this historically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Furthermore, even when African American women are receiving trauma treatment, they may be less willing to discuss trauma exposures, such as sexual assault, particularly with a therapist who does not identify as African American [65]. To cope with trauma, women may employ maladaptive coping strategies, such as alcohol and marijuana misuse [66]. Given that women experiencing a trauma history were three times more likely to have poorer coping skills, coping skills education and support may be valuable additions to programs designed to help women who have experienced trauma.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Furthermore, even when African American women are receiving trauma treatment, they may be less willing to discuss trauma exposures, such as sexual assault, particularly with a therapist who does not identify as African American [65]. To cope with trauma, women may employ maladaptive coping strategies, such as alcohol and marijuana misuse [66]. Given that women experiencing a trauma history were three times more likely to have poorer coping skills, coping skills education and support may be valuable additions to programs designed to help women who have experienced trauma.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…A meta-analytic study (C. Wang et al 2021) focusing on the mental health status of college students reported elevated levels of anxiety, depression, and stress. Students experiencing more depressive and anxiety symptoms were also found to be more prone to using alcohol and other substances as a means of coping (Singleton et al 2022).…”
Section: Introductionmentioning
confidence: 98%
“…Youths have been directly affected by social services and programs interruptions and disproportionately impacted by repressive measures (e.g., Gabriel et al, 2021). Beside these challenges, many young Black people have been impacted by the financial strain associated with COVID‐19 while facing exacerbated mental health challenges raised by the racial reckoning (e.g., Singleton et al, 2022).…”
mentioning
confidence: 99%